The Role of Digital Marketing in the Promotional Activities of Congresses within the Scope of Event Marketing (Third Sector Social Economic Review, 2025)
The aim is to influence potential conference participants and ensure that the conference is chosen over similar conferences by using various communication tools to promote conferences/events held for purposes such as conveying scientific developments, sharing new information, and socialising. The study examined the role of digital communication tools used for promotional announcements prior to the event, as well as for informing and reminding participants during the event, in relation to the demographic characteristics of the target audience. In this study, designed as quantitative research and employing the survey method as the data collection technique, a Likert-type scale developed by the researchers was used. Following statistical analyses conducted during the scale development process, a 16-item scale was prepared, consisting of a three-factor structure: ‘Website & Email Marketing, Social Media Marketing, and Mobile Marketing & SMS’. It is anticipated that the scale will enable a multidimensional examination of participants' levels of importance attached to digital marketing communication tools used in event promotion. A total of 833 medical doctors were reached using purposive sampling; the data were tested using the T-test and ANOVA analysis. The findings indicate that female doctors place greater importance on the use of digital marketing tools in promoting events than male doctors do; however, there was no significant difference in the level of importance placed on these tools across age groups, academic titles, and academic fields. Detailed comments are provided in the results section, and recommendations are made to businesses.
Keywords: Event; Event Marketing; Digital Marketing; Communication; Promotion